Professional risks: the Brazilian capital journalists perception on their work during the pandemic - Martins, Bárbara Nogueira; Oliveira-Costa, Mariella Silva de (Revista Española de Comunicación en Salud, 2023)
Introduction: Health journalism had a key role in the COVID-19 pandemic around the world. In Brazil, the misinformation and scientific uncertainty had an impact on physical and mental health journalists. Objective: To understand the perception of journalists in the capital of Brazil about their work during the COVID-19 pandemic. Methodology: Qualitative, exploratory and descriptive research, with content analysis of online interviews with journalists who work with topics on COVID-19 during the pandemic. Results: The life and working conditions of journalists in the pandemic were changed, with the need for more caution to explain, disseminate and update people about COVID-19. There was more work, difficulties and slowness in gathering information. The home office, the use of new technologies for preparing and editing the news were also mentioned as a positive thing. Conclusion: The pandemic changed the way of Brazilian journalism, with challenges and opportunities that must be accompanied by the managers, workers and health communication researchers.
Keywords: health communication; journalism; pandemia; covid-19; work